Planning in advance: exploring end-of-life hopes and fears among healthy young people. (3rd July 2021) - Dark-Freudeman, Alissa; Terry, Christian; Fleming, Jason; Hollander, John; Bensadon, Benjamin
ABSTRACT: Discussions regarding end-of-life (EOL) preferences often occur late in the course of a disease leading to rushed clinical decisions misaligned with patient goals. Thus, the purpose of the current study was to identify EOL goals among a healthy sample of young adults (N = 305) through a possible selves framework. Common EOL hopes included: having loved ones present, closure, and living a full life. Common EOL fears included: pain and suffering, specific types of death, and dying alone. Hopes and fears related to religiosity were rare. Overall, participants felt more confident attaining EOL hopes than avoiding EOL fears. Even in young adulthood, when concerns related to ageing, illness, and dying are not acute, individuals have clear ideas regarding what they do and do not want to experience at their end of life. Conversations regarding EOL preferences should therefore be initiated with adult patients of all ages. Clinically, end-of-life training and care should integrate these psychological insights.